Mobile internet big data technology-based echo loss measurement method of optical communication system. (July 2022) - Gao, Yan; Shang, Tao; Ma, Lining
Abstract: The paper proposes a method to analyze the process of echo loss in an optical communication system in combination with mobile internet big data technology. The optical echo loss tester shall include the output connector, the standard reflector and the automatic unite to process and display the device to be measured. Using mode-coupling theory, we can calculate the loss when a light in an optical fiber flows through a fiber optic connector under various effect variables; then analytical formulas are developed, to calculate insertion and echo loss in a real-life situation. In this research, we propose a method for measuring echo loss in optical communication systems using mobile internet big data technology. The effect of this method is evaluated combined with the simulation test, based on the research carried out by research. The optical communication echo loss measurement based on mobile Internet of Things big data technology has some influence.